Structure-Activity Relationship of PAD4 Inhibitors and Their Role in Tumor Immunotherapy - Yijiang Jia; Renbo Jia; Ayijiang Taledaohan; Yanming Wang; Yuji Wang (MDPI AG, 2024)
Protein arginine deiminase 4 (PAD4) plays an important role in cancer progression by participating in gene regulation, protein modification, and neutrophil extracellular trap (NET) formation. Many reversible and irreversible PAD4 inhibitors have been reported recently. In this review, we summarize the structure-activity relationships of newly investigated PAD4 inhibitors to bring researchers up to speed by guiding and describing new scaffolds as optimization and development leads for new effective, safe, and selective cancer treatments. In addition, some recent reports have shown evidence that PAD4 inhibitors are expected to trigger antitumor immune responses, regulate immune cells and related immune factors, enhance the effects of immune checkpoint inhibitors, and enhance their antitumor efficacy. Therefore, PAD4 inhibitors may potentially change tumor immunotherapy and provide an excellent direction for the development and clinical application of immunotherapy strategies for related diseases.